The Effects of Islamic Financial Literacy and Tam on the Intention of FEB UB Students to Pay Digital Zakat - Salma Ainayya Mumtaz; Moh. Athoillah (Islamic Economics and finance in Focus, 2025)
Indonesia is a country with a majority Muslim population that has a very large potential for zakat, infak, and sedekah. However, the realization of ZIS fund collection is still not optimal. The existence of a digital platform is expected to help increase the amount of ZIS fund collection. The aim of this research is to analyze the factors that influence student of the Faculty of economicss and Business Universitas Brawijaya's interest in conducting ZIS transactions through digital platforms. This study uses a quantitative method with SEM-PLS analysis. The sampling was conducted using purposive sampling techniques with the sample criteria being Muslim students of Faculty of economicss and Business Universitas Brawijaya with 101 participants. The results of this study indicate that Islamic financial literacy and perceived usefulness have a negative and insignificant impact on the interest in issuing ZIS. Meanwhile, the perception of ease of use and attitude have a positive and significant impact on the interest in issuing ZIS. Furthermore, attitudes do not moderate Islamic financial literacy towards the interest in issuing ZIS, whereas attitudes can moderate the perception of usefulness and the perception of ease of use towards the interest in issuing ZIS.